KINERJA ANGGOTA DPRD PROVINSI JAWA TENGAH PERIODE 2009-2014 - Sulistyowati Sulistyowati (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2015)
Performance periode 2009-2014 House of Representatives has not been satisfactory the public society. Although already using three main function council, namely  a legislative function, budgetary function, and monitoring functions.  This is evident from the results of a survey conducted by the Research and Development from Kompas, one of national newspapers as well as by internal House of Representatives itself. The result showed that the legislative function in generating regional regulations is always below from the Regional Legislation target. In years 2011 only able to set 5 piece of regional regulations. For monitoring function, council manage to find accountability performance report “LKPJ” governor in 2010 is copy paste from accountability statement report “LKPJ” last year. Parliament budget function indicates that his role is weak, because the executive is very instrumental in setting the Regional Representative Assembly central Java budget.